AKTIVITAS ANTIMICROBIAL EKSTRAK ETANOL BIJI GANITRI (Elaeocarpus sphaericus Schum.) TERHADAP PERTUMBUHAN BAKTERI PATOGEN - Hasyim As’ari; Tristi Indah Dwi Kurnia; N. Nurchayati (BIOEDUKASI, 2016)
The seed ethanol extracts ganitri (Elaeocarpus sphaericus Schum.) were tested for their antimicrobial activities against Shigella dysenteriae, Salmonella typhi, and Escherichia coli. At concentrations 10-50% the seed ethanol extracts ganitri effectively inhibited the growth of all tested bacteria as shown by the wide clear zones which varied from 0,026 to 0,996 cm 2 . Wide clear zone at concentration 50% extract can be categorized as high in E. coli, and moderate for Shigella dysenteriae and Salmonella typhi. While the minimum inhibitory concentration (MIC) the seed ethanol extracts ganitri same for all tested bacteria at concentration 1% extract. Keywords: Ganitri seed, antimicrobial, concentration, MIC